2021
DOI: 10.5114/biolsport.2021.109451
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 lockdown on match-activity and physical performance in professional football referees

Abstract: To investigate the effect of COVID-19 lockdown on match-play metrics in professional football referees during official matches of the Spanish professional leagues. Forty-two professional football referees from the First (n = 20) and Second Division (n = 22) were monitored during 564 official games using Global Positioning System (GPS) technology. Data of matches before lockdown were compared to matches after resumption of the competition. Compared to pre-lockdown, in the referees of the First Division there wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…In this study, the ACC and DEC (total numbers or peak values) were analysed according to their intensity, as has been conducted in previous studies [ 19 ]. In addition, if we consider the results in these variables, these female referees had lower values than male football referees in Spanish First and Second Division [ 18 ]. In addition, this study is in line with other studies which found that field football referees had similar performance to football players [ 23 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the ACC and DEC (total numbers or peak values) were analysed according to their intensity, as has been conducted in previous studies [ 19 ]. In addition, if we consider the results in these variables, these female referees had lower values than male football referees in Spanish First and Second Division [ 18 ]. In addition, this study is in line with other studies which found that field football referees had similar performance to football players [ 23 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…From a practical perspective, quantifying the load experienced by female football referees is necessary for gaining a better understanding of match demands and their performance during the season [ 17 ]. The referee’s performance can be evaluated through the different battery of fitness tests to assess their football-related fitness levels [ 18 ]. Previous studies have examined the correlation between certain match performance variables and results of fitness tests in male international football referees [ 19 ], and the results revealed that a high sprint and cardiovascular fitness level could be relevant to the performance of male referees during matches.…”
Section: Introductionmentioning
confidence: 99%
“…They must be in good physical and mental condition to make the right decision. On the one hand, the lockdown of COVID-19 has made football referees less physically active and lack organized training and competition, which may lead to a decline in physical fitness and professional skills [ 27 , 28 ]. On the other hand, because the salary of football referees is related to the number of matches they play, the temporary suspension of work causes them to suffer financial pressure and uncertainty in their career development.…”
Section: Introductionmentioning
confidence: 99%
“…It is apparent that the effects of lockdown are more severe and multifaceted than just a scheduled absence from training activities, and they can act as a negative stressor for many athletes indicating that special considerations are needed when athletes return to sport in the event of significant levels of detraining [ 24 , 25 , 26 ]. Regarding this, decrements in performance have been extensively proven during and after training restriction due to the ongoing pandemic conditions in age-group athletes, in individual and team sports, in sprint and endurance disciplines, at amateur and elite level [ 24 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%